Pengaruh Pemanfaatan Media Sosial, Pendidikan Kewirausahaan dan Pengetahuan Akuntansi Terhadap Minat Mahasiswa Berwirausaha (Studi Kasus Mahasiswa Prodi Akuntansi Fakultas Ekonomi dan Bisnis dan Mahasiswa Prodi Administrasi Bisnis Fakultas Ilmu Administrasi Universitas Islam Malang) - Muhammad Iqbal Achdiyat; Maslichah Maslichah; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Entrepreneurial interest is the desire, interest, and individual willingness to work hard to meet their needs and run their own business without fear of the risks that will occur. This study aims to determine the effect of using social media, entrepreneurship education and accounting knowledge on students' interest in entrepreneurship both simultaneously and partially. The research method uses a correlational method with a quantitative approach. The data used is primary data using a questionnaire. The population in this study were accounting and business administration students class 2019 - 2020, Faculty of Economics and Business and Faculty of Administrative Sciences, Islamic University of Malang, and the sample was taken using purposive sampling, the data obtained was 90 respondents. Data analysis using multiple linear regression analysis. While data processing uses IBM SPSS 26. The results of the analysis show that the use of social media has a positive and significant effect on student interest in entrepreneurship, entrepreneurship education has no effect on student interest in entrepreneurship and accounting knowledge has a positive and significant effect on student interest in entrepreneurship.Keywords: Utilization of Social Media, Entrepreneurship Education, Accounting Knowledge and Student Interests in Entrepreneurship